A diamond / copper composite material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611219277.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]目前,金刚石/铜复合材料的制备方法主要包括粉末冶金法、熔渗法、放电等离子烧结法等,但现有技术普遍存在以下瓶颈:一是金刚石与铜基体的本征润湿性极差、界面结合强度低、存在孔隙等缺陷,导致复合材料导热性能大幅下降;二是复合材料致密度难以提升,微观组织中易出现金刚石团聚、氧化相夹杂等问题;三是复合材料二次加工性能差,无法形成复杂构件
[0089]本发明的有益效果是:本发明中的金刚石/铜复合材料通过引入纳米Mo颗粒作为调控相,可通过界面反应优化界面结合、抑制金刚石石墨化,提升复合材料的界面结合力,获得高致密度、高导热率和较高力学性能的复合材料,可广泛应用于航空航天、电子封装、新能源等领域的高端散热构件制造。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal matrix composite technology, and specifically relates to a diamond / copper composite material, its preparation method, and its application. Background Technology
[0002] Diamond / copper composites are core materials for solving heat dissipation problems in high-power electronic devices and precision aerospace instruments. Their performance directly depends on the quality of the interfacial bonding between diamond and the copper matrix, the density of the composite material, and the uniformity of its microstructure.
[0003] Currently, the main methods for preparing diamond / copper composite materials include powder metallurgy, melt infiltration, and spark plasma sintering. However, existing technologies generally suffer from the following bottlenecks: First, the intrinsic wettability between diamond and the copper matrix is extremely poor, the interfacial bonding strength is low, and defects such as pores exist, leading to a significant decrease in the thermal conductivity of the composite material. Second, it is difficult to improve the density of the composite material, and problems such as diamond agglomeration and oxide phase inclusions easily occur in the microstructure. Third, the composite material has poor secondary processing performance and cannot form complex components.
[0004] The above-mentioned problems limit the application of diamond / copper composite materials in heat dissipation for high-power electronic devices and precision aerospace instruments. Summary of the Invention
[0005] In order to overcome at least one of the technical problems existing in the prior art, one of the objectives of the present invention is to provide a diamond / copper composite material.
[0006] The second objective of this invention is to provide a method for preparing diamond / copper composite materials.
[0007] The third objective of this invention is to provide a heat dissipation component.
[0008] The fourth objective of this invention is to provide applications of the aforementioned diamond / copper composite material in the fields of aerospace, electronic packaging, or new energy.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a diamond / copper composite material comprising a copper matrix and diamond particles and nano-Mo particles distributed in the copper matrix; The mass of the nano-Mo particles is 0.3-3% of the total mass of the diamond / copper composite material; The mass of the diamond particles is 25-50% of the total mass of the diamond / copper composite material; The diamond / copper composite material contains 47-74.7% copper by mass.
[0010] This invention uses nano-Mo particles as the interface control phase. The nano-Mo particles can form a Mo2C alloy transition layer at the interface between diamond and copper matrix, which effectively improves the wettability of diamond and copper matrix, solves the core problem of weak interfacial bonding between the two, and at the same time inhibits the graphitization transformation of diamond during high-temperature preparation process, thus preserving the ultra-high thermal conductivity of diamond.
[0011] In some embodiments of the present invention, a Mo2C alloy transition layer is provided between the diamond particles and the copper substrate.
[0012] In some embodiments of the present invention, the mass of the nano-Mo particles is any one of 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3% of the total mass of the diamond / copper composite material, or a range formed by any two of these values.
[0013] In some embodiments of the present invention, the mass of the diamond particles is any one of 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50% of the total mass of the diamond / copper composite material, or a range formed by any two of these values.
[0014] In some embodiments of the present invention, the mass percentage of copper in the diamond / copper composite material is any value or a range formed by any two of the following: 47%, 50%, 52%, 55%, 57%, 60%, 62%, 65%, 67%, 70%, 72%, 74%, and 74.7%.
[0015] In some embodiments of the present invention, the density of the diamond / copper composite material is ≥99%.
[0016] In some embodiments of the present invention, the thermal conductivity of the diamond / copper composite material is 600-750 W / (m·K); in some embodiments of the present invention, the thermal conductivity of the diamond / copper composite material is any value or a range formed by any two of the following: 600 W / (m·K), 620 W / (m·K), 640 W / (m·K), 650 W / (m·K), 660 W / (m·K), 680 W / (m·K), 700 W / (m·K), 720 W / (m·K), 740 W / (m·K), 750 W / (m·K), 760 W / (m·K).
[0017] In some embodiments of the present invention, the tensile strength of the diamond / copper composite material is 200-300 MPa; in some embodiments of the present invention, the tensile strength of the diamond / copper composite material is any value of 200 MPa, 220 MPa, 240 MPa, 250 MPa, 260 MPa, 280 MPa, 300 MPa, or a range formed by any two of these values.
[0018] In some embodiments of the present invention, the flexural strength of the diamond / copper composite material is 300-400 MPa; in some embodiments of the present invention, the flexural strength of the diamond / copper composite material is any value or a range formed by any two of the following: 300 MPa, 310 MPa, 320 MPa, 330 MPa, 340 MPa, 350 MPa, 360 MPa, 370 MPa, 380 MPa, 390 MPa, and 400 MPa.
[0019] In some embodiments of the present invention, the average particle size of the nano-Mo particles is 30-150 nm; in some embodiments of the present invention, the average particle size of the nano-Mo particles is 80-120 nm.
[0020] In some embodiments of the present invention, the average particle size of the diamond particles is 80-120 μm.
[0021] The second aspect of the present invention provides a method for preparing the diamond / copper composite material described in the first aspect of the present invention, comprising the following steps: The raw materials, including copper powder, diamond powder and molybdenum powder, are subjected to two-stage grinding to obtain composite powder; The composite powder is mixed with a dispersant and a binder and then kneaded to obtain a composite material; the composite material is then subjected to powder injection molding to obtain a preform. The shaped green body is degreased and then reduced sintered in a hydrogen atmosphere to obtain a sintered green body. The sintered green body is subjected to hot isostatic pressing and then cooled to obtain the diamond / copper composite material. The reduction sintering temperature is ≤1100℃.
[0022] In some embodiments of the present invention, the diamond powder, copper powder and molybdenum powder need to be vacuum dried before use to remove moisture and impurities adsorbed on the powder surface, and then sieved after vacuum drying before use.
[0023] In some embodiments of the present invention, the temperature of the vacuum drying process is 70-100°C.
[0024] In some embodiments of the present invention, the drying time of the vacuum drying process is 1-2 hours.
[0025] In some embodiments of the present invention, the vacuum degree of the vacuum drying process is ≤10. -3 Pa.
[0026] In some embodiments of the present invention, the average particle size of the diamond powder is 80-120 μm.
[0027] In some embodiments of the present invention, the purity of the diamond powder is ≥99.9%.
[0028] In some embodiments of the present invention, the average particle size of the molybdenum powder is 30-150 nm; in some embodiments of the present invention, the average particle size of the molybdenum powder is 80-120 nm.
[0029] In some embodiments of the present invention, the purity of the molybdenum powder is ≥99.5%.
[0030] In some embodiments of the present invention, the average particle size of the copper powder is 10-50 μm.
[0031] In some embodiments of the present invention, the purity of the copper powder is ≥99.9%.
[0032] In some embodiments of the present invention, sieving refers to screening using a 200-300 mesh sieve to remove agglomerated particles and ensure the dispersibility of the raw materials.
[0033] In some embodiments of the present invention, the reduction sintering is carried out in a reduction sintering furnace.
[0034] In some embodiments of the present invention, the reduction sintering specifically involves: under a hydrogen atmosphere, first heating the degreased shaped blank to 750-850°C for a first sintering, and then heating to 900-1020°C for a second sintering. The first sintering is mainly for hydrogen reduction reaction to remove oxide phases (CuO, MoO3, etc.) from the blank, while the second sintering is mainly for promoting the uniform distribution of nano-Mo particles at the interface between the diamond and copper matrix, forming a Mo2C alloy transition layer, and optimizing the interfacial bonding.
[0035] In some embodiments of the present invention, the temperature of the first sintering is any value of 750°C, 760°C, 780°C, 800°C, 810°C, 820°C, 840°C, 850°C, or a range formed by any two of them.
[0036] In some embodiments of the present invention, the heating rate of the first sintering is 8-12℃ / min; in some embodiments of the present invention, the heating rate of the first sintering is any value of 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, 12℃ / min or a range formed by any two of them.
[0037] In some embodiments of the present invention, the holding time for the first sintering is 30-60 min; in some embodiments of the present invention, the holding time for the first sintering is any value of 30 min, 40 min, 50 min, 60 min, or a range formed by any two of them.
[0038] In some embodiments of the present invention, the hydrogen flow rate during the first sintering is 5-10 mL / min; in some embodiments of the present invention, the hydrogen flow rate during the first sintering is any value of 5 mL / min, 6 mL / min, 7 mL / min, 8 mL / min, 9 mL / min, 10 mL / min, or a range formed by any two of these values.
[0039] In some embodiments of the present invention, the heating rate of the second sintering is 5-8°C / min; in some embodiments of the present invention, the heating rate of the second sintering is any value of 5mL / min, 6mL / min, 7mL / min, 8mL / min, or a range formed by any two of them.
[0040] In some embodiments of the present invention, the holding time for the second sintering is 2-3 hours.
[0041] In some embodiments of the present invention, the hot isostatic pressing process is performed in a hot isostatic press.
[0042] In some embodiments of the present invention, the hot isostatic pressing process is performed under the protection of a protective gas.
[0043] In some embodiments of the present invention, the protective gas used in the hot isostatic pressing process is selected from at least one gas selected from nitrogen, argon, helium, and xenon. In some embodiments of the present invention, the purity of the protective gas is ≥99.99%.
[0044] In some embodiments of the present invention, the temperature of the hot isostatic pressing treatment is 900-1000°C; in some embodiments of the present invention, the temperature of the hot isostatic pressing treatment is any value of 900°C, 920°C, 940°C, 950°C, 960°C, 980°C, 1000°C or a range formed by any two of them.
[0045] In some embodiments of the present invention, the pressure of the hot isostatic pressing is 80-150 MPa; in some embodiments of the present invention, the pressure of the hot isostatic pressing is any value of 80 MPa, 100 MPa, 120 MPa, 140 MPa, 150 MPa or a range formed by any two of them.
[0046] In some embodiments of the present invention, the holding time of the hot isostatic pressing treatment is 2-4 hours.
[0047] In some embodiments of the present invention, the pressure increase rate of the hot isostatic pressing treatment is 5~10 MPa / min.
[0048] Hot isostatic pressing is mainly used to make the green body more compact, eliminate the porosity inside the green body, further improve the interfacial bonding strength and the density of the composite material, so that the density of the composite material reaches more than 99%.
[0049] In some embodiments of the present invention, the secondary grinding is as follows: first, ball milling is performed at a ball milling rate of 50-180 r / min, and then ball milling is performed at a ball milling rate of 150-250 r / min under the protection of protective gas to obtain the composite powder.
[0050] In some embodiments of the invention, the first ball milling is performed in a light ball mill.
[0051] In some embodiments of the present invention, the ball milling time for the first ball milling is 3-8 hours.
[0052] In some embodiments of the present invention, the first ball milling is performed using zirconium oxide grinding media.
[0053] In some embodiments of the present invention, the second ball milling is performed in a planetary ball mill.
[0054] In some embodiments of the present invention, the protective gas used in the second ball milling is selected from at least one gas selected from nitrogen, argon, helium, and xenon. In some embodiments of the present invention, the purity of the protective gas is ≥99.99%.
[0055] In some embodiments of the present invention, the pressure of the protective gas during the second ball milling is 0.3-1 MPa.
[0056] In some embodiments of the present invention, the flow rate of the protective gas during the second ball milling is 2-5 mL / min to prevent oxidation of the raw materials.
[0057] In some embodiments of the present invention, the second ball milling is performed using zirconium oxide grinding media.
[0058] In some embodiments of the present invention, the ball-to-material ratio during the second ball milling is (10-20):1.
[0059] In some embodiments of the present invention, the second ball milling time is 2-4 hours.
[0060] In some embodiments of the present invention, the mixing is carried out under the protection of a protective gas.
[0061] In some embodiments of the present invention, the protective gas used during internal mixing is selected from at least one gas selected from nitrogen, argon, helium, and xenon. In some embodiments of the present invention, the purity of the protective gas is ≥99.99%.
[0062] In some embodiments of the present invention, the mixing temperature is 120-170°C; in some embodiments of the present invention, the mixing temperature is any value of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or a range formed by any two of them.
[0063] In some embodiments of the present invention, the mixing time is 20-50 minutes.
[0064] In some embodiments of the present invention, the stirring speed of the intensive mixing is 30-50 r / min.
[0065] In some embodiments of the present invention, the composite material is obtained by mixing and kneading the composite powder with a dispersant and a binder in an atmosphere mixer, and then cooling it in the furnace to 20-40°C.
[0066] In some embodiments of the present invention, the mass of the dispersant is 0.1-0.5% of the mass of the composite powder.
[0067] In some embodiments of the present invention, the dispersant includes at least one of stearic acid and palmitic acid.
[0068] In some embodiments of the present invention, the mass of the binder is 10-20% of the mass of the composite powder.
[0069] In some embodiments of the present invention, the adhesive is a paraffin-polyethylene-stearic acid composite adhesive.
[0070] In some embodiments of the present invention, the mass ratio of paraffin, polyethylene and stearic acid in the paraffin-polyethylene-stearic acid composite adhesive is (12-18):(3-8):1; in some embodiments of the present invention, the mass ratio of paraffin, polyethylene and stearic acid in the paraffin-polyethylene-stearic acid composite adhesive is (13-16):(4-6):1.
[0071] Dispersants and binders ensure that diamond powder, molybdenum powder and copper powder are evenly dispersed, preventing powder agglomeration.
[0072] In some embodiments of the present invention, the powder injection molding is performed in a powder injection molding machine.
[0073] In some embodiments of the present invention, the injection temperature of the powder injection molding is 120-180°C; in some embodiments of the present invention, the injection temperature of the powder injection molding is any value of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a range formed by any two of them.
[0074] In some embodiments of the present invention, the injection pressure of the powder injection molding is 50-150 MPa; in some embodiments of the present invention, the injection pressure of the powder injection molding is any value or a range formed by any two of 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, and 150 MPa.
[0075] In some embodiments of the present invention, the holding time of the powder injection molding is 10-30 seconds.
[0076] In some embodiments of the present invention, the powder injection molding is performed as follows: the composite material is added to a powder injection molding machine, and injected into a preset mold under the conditions of injection temperature of 120-180℃, injection pressure of 50-150MPa, and holding time of 10-30s. After cooling to room temperature, the material is demolded to obtain a molded blank.
[0077] In some embodiments of the present invention, the degreasing is performed by first degreasing in air at 120-180°C, and then by a second degreasing under a protective gas at 400-600°C. This step-by-step degreasing method thoroughly removes the binder from the green body and reduces porosity defects.
[0078] In some embodiments of the present invention, the protective gas for the second degreasing is selected from at least one of nitrogen, argon, and helium.
[0079] In some embodiments of the present invention, the flow rate of the protective gas for the second degreasing is 3-10 mL / min.
[0080] In some embodiments of the present invention, the temperature of the first degreasing is any value of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or a range formed by any two of these values.
[0081] In some embodiments of the present invention, the heating rate for the first degreasing is 5~10℃ / min.
[0082] In some embodiments of the present invention, the holding time for the first degreasing is 2-4 hours. The first degreasing mainly removes low-melting-point binders from the green body.
[0083] In some embodiments of the present invention, the temperature of the second degreasing is any value of 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, or a range formed by any two of these values.
[0084] In some embodiments of the present invention, the heating rate of the second degreasing is 10~15℃ / min.
[0085] In some embodiments of the present invention, the second degreasing is held for 3-6 hours to remove the high-melting-point binder from the green body, and a degreased green body is obtained after the degreasing is completed.
[0086] In some embodiments of the present invention, the cooling rate is 5-10℃ / min. Using this cooling rate can prevent thermal stress cracks from forming in the composite material.
[0087] A third aspect of the present invention provides a heat dissipation component made of the diamond / copper composite material described in the first aspect of the present invention.
[0088] The fourth aspect of the present invention provides the application of the diamond / copper composite material described in the first aspect of the present invention in the fields of aerospace, electronic packaging or new energy.
[0089] The beneficial effects of this invention are: by introducing nano-Mo particles as a regulating phase, the diamond / copper composite material of this invention can optimize the interfacial bonding and inhibit diamond graphitization through interfacial reaction, thereby improving the interfacial bonding force of the composite material and obtaining a composite material with high density, high thermal conductivity and high mechanical properties. It can be widely used in the manufacturing of high-end heat dissipation components in aerospace, electronic packaging, new energy and other fields.
[0090] The preparation method in this invention utilizes a complete process of powder injection molding, debinding sintering, hydrogen reduction sintering, and hot isostatic pressing densification to fully leverage the regulatory effect of nano-Mo particles, achieving high density, high interfacial bonding strength, and excellent thermal conductivity in diamond / copper composite materials. Furthermore, the process is simple, low-cost, highly efficient, and can be mass-produced. Attached Figure Description
[0091] Figure 1This is a process flow diagram of the preparation method of the present invention.
[0092] Figure 2 This is a scanning electron microscope image of the composite powder obtained after two-stage mixing in Example 1.
[0093] Figure 3 This is a cross-sectional scanning electron microscope image of the diamond / copper composite material prepared in Example 1. Detailed Implementation
[0094] The specific implementation of the present invention will be further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described in detail below are those that can be implemented or understood by those skilled in the art by referring to the prior art. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0095] like Figure 1 As shown, this invention provides a method for preparing diamond / copper composite materials based on nano-Mo particles, comprising the following steps: (1) Raw material pretreatment: Copper powder, diamond powder and molybdenum powder are respectively subjected to vacuum drying pretreatment to remove surface adsorbed moisture and impurities. The vacuum drying temperature is 70-100℃, the drying time is 1-2h, and the vacuum degree is ≤10. -3 Pa; after vacuum drying, pass through a 200-300 mesh sieve for later use.
[0096] (2) Powder classification and mixing: First, pretreated pure copper powder, diamond powder, and molybdenum powder are added to a light ball mill for premixing. The speed of the light ball mill is controlled at 50~180 r / min, and the premixing time is 3~8 h to obtain a preliminary mixed powder. Then, the preliminary mixed powder is transferred to a planetary ball mill, and argon gas is introduced as a protective atmosphere. The argon gas pressure is controlled at 0.3~1.0 MPa. Zirconia balls are added as grinding media, and the ball-to-material ratio is adjusted to 10:1~20:1. The speed of the planetary ball mill is controlled at 150~250 r / min, and the dispersion and mixing time is 2~4 h to obtain a uniform powder. The uniformly dispersed composite powder is added to an internal mixer under inert gas protection. A dispersant and a binder are added simultaneously. The mixing temperature is 120-170℃, the stirring speed is 30-50 r / min, and the mixing time is 20-50 min. After uniform mixing, the mixture is cooled to room temperature in the furnace to obtain a uniformly composed composite powder. The dispersant is stearic acid or palmitic acid, and the amount added is 0.1%-0.5% of the total mass of the raw materials. The binder is a paraffin-polyethylene-stearic acid composite binder, and the amount added is 10%-20% of the total mass of the raw materials. (3) Powder injection molding: The composite material powder obtained in step (2) is added to the powder injection molding machine. Under the conditions of injection temperature of 120~180℃, injection pressure of 50~150MPa and holding time of 10~30s, it is injected into the preset mold. After cooling to room temperature, it is demolded to obtain the molded blank. (4) Degreasing and sintering: The shaped green body obtained in step (3) is placed in a degreasing furnace and a segmented degreasing process is adopted. First, under an air atmosphere, the temperature is raised to 120-180℃ at a heating rate of 5-10℃ / min and held for 2-4 hours to remove the low melting point binder in the green body; then, under an inert gas protection, the temperature is raised to 400-600℃ at a heating rate of 10-15℃ / min and held for 3-6 hours to remove the high melting point binder in the green body. After degreasing, a degreased green body is obtained. (5) Hydrogen reduction sintering: The degreased green body obtained in step (4) is transferred to a reduction sintering furnace. A staged sintering process is adopted, and high-purity hydrogen is introduced. The hydrogen flow rate is 5~10mL / min. First, the temperature is raised to 750-850℃ at a heating rate of 8~12℃ / min and held for 30-60min to carry out the hydrogen reduction reaction and remove the oxide phase (CuO, MoO3, etc.) in the green body. Then, the temperature is raised to 900-1020℃ at a heating rate of 5~8℃ / min and held for 2-3h. At the same time, the uniform distribution of nano Mo particles at the diamond and copper matrix interface is promoted to form a Mo2C alloy transition layer and optimize the interface bonding. (6) Hot isostatic pressing densification: The reduced sintered green body obtained in step (5) is placed in a hot isostatic press. Under the protection of inert gas, the temperature is controlled at 900~1000℃, the pressure is 80~150MPa, and the holding time is 2~4h. Hot isostatic pressing densification treatment is carried out to eliminate the internal pores of the green body, further improve the interfacial bonding strength and the density of the composite material. After cooling to room temperature, diamond / copper composite material based on nano Mo particles is obtained.
[0097] The specific implementation of the present invention will be further described in detail below with reference to specific embodiments and comparative examples: Example 1 This example provides a method for preparing diamond / copper composite materials based on nano-Mo particles, the specific steps of which are as follows: (1) Pretreatment of raw material powder: Weigh the raw materials by mass percentage as follows: diamond powder (average particle size 100μm, purity 99.9%) 35%, nano Mo particles (average particle size 100nm, purity 99.5%) 1%, copper powder (average particle size 35μm, purity 99.9%) 64%; pretreat all raw material powders in a vacuum dryer at a drying temperature of 80℃ for 1h, with a vacuum degree ≤10 -3 Pa; After drying, each raw material is passed through a 200-mesh sieve; (2) Powder mixing: The dried raw materials were added to a light ball mill at a speed of 100 r / min and a premixing time of 4 h to obtain a preliminary mixed powder. The preliminary mixed powder was then transferred to a planetary ball mill, and argon gas was introduced as a protective atmosphere. The argon gas pressure was controlled at 0.6 MPa. Zirconia balls were added as grinding media, and the ball-to-material ratio (i.e., the mass ratio of grinding balls to preliminary mixed powder) was adjusted to 10:1. The speed of the planetary ball mill was controlled at 200 r / min and the dispersion and mixing time was 3 h to obtain a uniformly dispersed composite powder. Its scanning electron microscope image is shown below. Figure 2 As shown, by Figure 2 It can be seen that the composite powder after two-stage mixing has a uniform particle size and no obvious agglomeration. The nano Mo particles are uniformly dispersed between the copper powder and diamond. The uniformly dispersed composite powder is added to the mixing equipment of the internal mixer, and argon gas is introduced for protection (purity 99.99%, flow rate 5mL / min). At the same time, a dispersant and a binder are added. The dispersant is stearic acid, and the amount of dispersant added is 0.1% of the total mass of the composite powder. A paraffin-polyethylene-stearic acid composite binder (mass ratio of paraffin, polyethylene and stearic acid is 70:25:5) is added, accounting for 15% of the total mass of the composite powder. Under the protection of inert gas argon, the mixing temperature is 150℃, the stirring speed is 45r / min, and the mixing time is 40min. After being mixed evenly, the mixture is cooled to room temperature in the furnace to obtain a composite powder with uniform composition. (3) Powder injection molding: Add the composite material powder obtained in step (2) into the injection molding machine, set the injection temperature to 150℃, the injection pressure to 100MPa, and the holding time to 20s, inject it into the mold, cool it to room temperature and demold to obtain the molded blank. (4) Degreasing and sintering: The shaped green body is placed in a degreasing furnace. First, in an air atmosphere, the temperature is raised to 150°C at 8°C / min and held for 3 hours to remove the low-melting-point binder. Then, argon gas (purity 99.99%, flow rate 8 mL / min) is introduced and the temperature is raised to 500°C at 12°C / min and held for 4 hours to remove the high-melting-point binder, thus obtaining a degreased green body. (5) Hydrogen reduction sintering: The degreased green body is transferred to a reduction sintering furnace, high-purity hydrogen gas (flow rate 10 mL / min) is introduced, the temperature is raised to 800℃ at 10℃ / min, and held for 60 min to carry out the hydrogen reduction reaction, remove the oxide phase and form a Mo2C transition layer; then the temperature is raised to 1000℃ at a heating rate of 7℃ / min, and held for 2 h to optimize the interface bonding and obtain the reduction sintered green body; (6) Hot isostatic pressing densification: The reduced sintered green body was placed in a hot isostatic press, and argon gas (purity 99.99%) was introduced. The pressure was increased to 130 MPa at 8 MPa / min, and the temperature was increased to 1000℃ and held for 3 hours. Then, the temperature was decreased to room temperature at 8℃ / min to obtain the diamond / copper composite material in this example. The scanning electron microscope image of the cross section of the diamond / copper composite material prepared in this example is shown below. Figure 3 As shown. By Figure 3 It can be seen that the diamond / copper composite material prepared by the present invention has a dense cross-section with no obvious pores and cracks, and the diamond is tightly bonded to the copper matrix with no obvious defects at the interface.
[0098] The diamond / copper composite material prepared in this example has a density of 99.2%, a thermal conductivity of 682 W / (m·K), a tensile strength of 220 MPa, a flexural strength of 322 MPa, and a tight interfacial bond with no obvious porosity or debonding defects, as shown in Table 1 below.
[0099] Example 2 This example provides a method for preparing diamond / copper composite materials based on nano-Mo particles, the specific steps of which are as follows: (1) Pretreatment of raw material powder: Weigh the raw materials by mass percentage as follows: diamond powder (average particle size 100μm, purity 99.9%) 45%, nano Mo particles (average particle size 100nm, purity 99.5%) 2%, copper powder (average particle size 35μm, purity 99.9%) 53%; pretreat in a vacuum dryer at a drying temperature of 80℃ for 1h, with a vacuum degree ≤10 -3 Pa; After drying, each raw material is passed through a 200-mesh sieve; (2) Powder mixing: The dried raw materials are added to a light ball mill at a speed of 100 r / min and a premixing time of 4 h to obtain a preliminary mixed powder. The preliminary mixed powder is then transferred to a planetary ball mill, where argon gas is introduced as a protective atmosphere and the argon gas pressure is controlled at 0.6 MPa. Zirconia balls are added as grinding media, and the ball-to-material ratio is adjusted to 15:1. The speed of the planetary ball mill is controlled at 250 r / min and the dispersion mixing time is 3 h to obtain a uniformly dispersed composite powder. The uniformly dispersed composite powder is then added to a mixing equipment in a mixer. Argon gas (99.99% purity, flow rate 5 mL / min) was introduced for protection. At the same time, a dispersant and a binder were added. The dispersant was stearic acid, and the mass of the dispersant added was 0.1% of the total mass of the composite powder. A paraffin-polyethylene-stearic acid composite binder (the ratio of paraffin, polyethylene and stearic acid was the same as in Example 1) was added at 15% of the total mass of the composite powder. Under the protection of inert gas, the mixing temperature was 160°C, the stirring speed was 50 r / min, and the mixing time was 40 min. After mixing evenly, the mixture was cooled to room temperature in the furnace to obtain a composite powder with uniform composition. (3) Powder injection molding: Add the composite material powder obtained in step (2) into the injection molding machine, set the injection temperature to 150℃, the injection pressure to 100MPa, and the holding time to 20s, inject it into the mold, cool it to room temperature and demold to obtain the molded blank. (4) Degreasing and sintering: The shaped green body is placed in a degreasing furnace. First, in an air atmosphere, the temperature is raised to 150°C at 8°C / min and held for 3 hours to remove the low-melting-point binder. Then, argon gas (purity 99.99%, flow rate 8 mL / min) is introduced and the temperature is raised to 500°C at 12°C / min and held for 4 hours to remove the high-melting-point binder, thus obtaining a degreased green body. (5) Hydrogen reduction sintering: The degreased green body is transferred to a reduction sintering furnace, high-purity hydrogen gas (flow rate 10 mL / min) is introduced, the temperature is raised to 850℃ at 8℃ / min, and held for 60 min to carry out the hydrogen reduction reaction, remove the oxide phase and form a Mo2C transition layer; then the temperature is raised to 1020℃ at a heating rate of 8℃ / min, and held for 3 h to optimize the interface bonding and obtain the reduction sintered green body; (6) Hot isostatic pressing densification: The reduced sintered blank is placed in a hot isostatic press, argon gas (purity 99.99%) is introduced, the pressure is increased to 130 MPa at 8 MPa / min, the temperature is increased to 1000℃, and the temperature is held for 3 hours. Then the temperature is reduced to room temperature at 8℃ / min to obtain the diamond / copper composite material in this example.
[0100] The diamond / copper composite material prepared in this example has a density of 99.5%, a thermal conductivity of 650 W / (m·K), a tensile strength of 242 MPa, a flexural strength of 327 MPa, and a tight interfacial bond with no obvious porosity or debonding defects, as shown in Table 1 below.
[0101] Comparative Example 1 This example provides a method for preparing diamond / copper composite materials based on nano-Mo particles, the specific steps of which are as follows: (1) Pretreatment of raw material powder: Weigh the raw materials by mass percentage as follows: diamond powder (average particle size 100μm, purity 99.9%) 35%, nano Mo particles (average particle size 100nm, purity 99.5%) 5%, copper powder (average particle size 35μm, purity 99.9%) 60%; pretreat in a vacuum dryer at a drying temperature of 80℃ for 1h, with a vacuum degree ≤10 -3 Pa; After drying, each raw material is passed through a 200-mesh sieve; (2) Powder mixing: The dried raw materials were added to a light ball mill at a speed of 100 r / min and a premixing time of 4 h to obtain a preliminary mixed powder. The preliminary mixed powder was then transferred to a planetary ball mill, and argon gas was introduced as a protective atmosphere. The argon gas pressure was controlled at 0.6 MPa. Zirconia balls were added as grinding media, and the ball-to-material ratio was adjusted to 10:14. The speed of the planetary ball mill was controlled at 200 r / min and the dispersion and mixing time was 3 h to obtain a uniformly dispersed composite powder. The uniformly dispersed powder was then added to a mixing equipment in a mixer and mixed with argon gas. Argon gas (99.99% purity, flow rate 5 mL / min) was introduced for protection. A dispersant and a binder were added simultaneously. The dispersant was stearic acid, and the amount of dispersant added was 0.1% of the total mass of the composite powder. A paraffin-polyethylene-stearic acid composite binder (the mass ratio of paraffin, polyethylene and stearic acid was the same as in Example 1) was added at 15% of the total mass of the composite powder raw materials. Under the protection of inert argon gas, the mixing temperature was 150°C, the stirring speed was 45 r / min, and the mixing time was 40 min. After mixing evenly, the mixture was cooled to room temperature in the furnace to obtain a composite powder with uniform composition. (3) Powder injection molding: Add the composite material powder obtained in step (2) into the injection molding machine, set the injection temperature to 150℃, the injection pressure to 100MPa, and the holding time to 20s, inject it into the mold, cool it to room temperature and demold to obtain the molded blank. (4) Degreasing and sintering: The shaped green body is placed in a degreasing furnace. First, in an air atmosphere, the temperature is raised to 150°C at 8°C / min and held for 3 hours to remove the low-melting-point binder. Then, argon gas (purity 99.99%, flow rate 8 mL / min) is introduced and the temperature is raised to 500°C at 12°C / min and held for 4 hours to remove the high-melting-point binder, thus obtaining a degreased green body. (5) Hydrogen reduction sintering: The degreased green body is transferred to a reduction sintering furnace, high-purity hydrogen gas (flow rate 10 mL / min) is introduced, the temperature is raised to 800℃ at 10℃ / min, and held for 60 min to carry out hydrogen reduction reaction, remove the oxide phase and form a Mo2C transition layer; then the temperature is raised to 1000℃ at a heating rate of 7℃ / min and held for 2 h to optimize the interface bonding; (6) Hot isostatic pressing densification: The reduced sintered green body is placed in a hot isostatic press, argon gas (purity 99.99%) is introduced, the pressure is increased to 130 MPa at 8 MPa / min, the temperature is increased to 1000℃, and the temperature is held for 3 hours. Then the temperature is reduced to room temperature at 8℃ / min to obtain diamond / copper composite material.
[0102] The diamond / copper composite material prepared in this example has a density of 99%, a thermal conductivity of 264 W / (m·K), a tensile strength of 156 MPa, and a flexural strength of 224 MPa, as shown in Table 1 below.
[0103] Comparative Example 2 This example provides a method for preparing diamond / copper composite materials based on nano-Mo particles, the specific steps of which include: (1) Pretreatment of raw material powder: Weigh the raw materials by mass percentage as follows: diamond powder (average particle size 100μm, purity 99.9%) 35%, nano Mo particles (average particle size 100nm, purity 99.5%) 0.2%, copper powder (average particle size 35μm, purity 99.9%) 64.8%; pretreat in a vacuum dryer at a drying temperature of 80℃ for 1h, with a vacuum degree ≤10 -3 Pa; After drying, each raw material is passed through a 200-mesh sieve; (2) Powder mixing: The dried raw materials are added to a light ball mill at a speed of 100 r / min and a premixing time of 4 h to obtain a preliminary mixed powder. The preliminary mixed powder is then transferred to a planetary ball mill, where argon gas is introduced as a protective atmosphere and the argon gas pressure is controlled at 0.6 MPa. Zirconia balls are added as grinding media, and the ball-to-material ratio is adjusted to 10:14. The speed of the planetary ball mill is controlled at 200 r / min and the dispersion mixing time is 3 h to obtain a uniformly dispersed composite powder. The uniformly dispersed composite powder is then added to a mixing equipment in a mixer. In the process, argon gas (99.99% purity, flow rate 5 mL / min) is introduced for protection. At the same time, a dispersant and a binder are added. The dispersant is stearic acid, and the amount of dispersant added is 0.1% of the total mass of the composite powder. A paraffin-polyethylene-stearic acid composite binder (the same as in Example 1) is added at 15% of the total mass of the composite powder. Under the protection of inert argon gas, the mixing temperature is 150°C, the stirring speed is 45 r / min, and the mixing time is 40 min. After mixing evenly, the mixture is cooled to room temperature in the furnace to obtain a composite powder with uniform composition. (3) Powder injection molding: Add the composite material powder to the injection molding machine, set the injection temperature to 150℃, the injection pressure to 100MPa, and the holding time to 20s, inject it into the mold, and demold it after cooling to room temperature to obtain the molded blank. (4) Degreasing and sintering: The shaped green body is placed in a degreasing furnace. First, in an air atmosphere, the temperature is raised to 150°C at 8°C / min and held for 3 hours to remove the low-melting-point binder. Then, argon gas (purity 99.99%, flow rate 8 mL / min) is introduced and the temperature is raised to 500°C at 12°C / min and held for 4 hours to remove the high-melting-point binder, thus obtaining a degreased green body. (5) Hydrogen reduction sintering: The degreased green body is transferred to a reduction sintering furnace, high-purity hydrogen gas (flow rate 10 mL / min) is introduced, the temperature is raised to 800℃ at 10℃ / min, and held for 60 min to carry out the hydrogen reduction reaction, remove the oxide phase and form a Mo2C transition layer; then the temperature is raised to 1000℃ at a heating rate of 7℃ / min and held for 2 h to optimize the interface bonding and obtain the reduction sintered green body; (6) Hot isostatic pressing densification: The reduced sintered green body is placed in a hot isostatic press, argon gas (purity 99.99%) is introduced, the pressure is increased to 130 MPa at 8 MPa / min, the temperature is increased to 1000℃, and the temperature is held for 3 hours. Then the temperature is reduced to room temperature at 8℃ / min to obtain diamond / copper composite material.
[0104] The diamond / copper composite material prepared in this example has a density of 99%, a thermal conductivity of 216 W / (m·K), a tensile strength of 134 MPa, and a flexural strength of 189 MPa, as shown in Table 1 below.
[0105] Comparative Example 3 This example provides a method for preparing diamond / copper composite materials based on nano-Mo particles, the specific steps of which are as follows: (1) Pretreatment of raw material powder: Weigh the raw materials by mass percentage as follows: diamond powder (average particle size 100μm, purity 99.9%) 45%, nano Mo particles (average particle size 100nm, purity 99.5%) 2%, copper powder (average particle size 35μm, purity 99.9%) 53%; pretreat in a vacuum dryer at a drying temperature of 80℃ for 1h, with a vacuum degree ≤10 -3 Pa; After drying, each raw material is passed through a 200-mesh sieve; (2) Powder mixing: The dried raw materials are added to a light ball mill at a speed of 100 r / min and a premixing time of 4 h to obtain a preliminary mixed powder. The preliminary mixed powder is then transferred to a planetary ball mill, where argon gas is introduced as a protective atmosphere and the argon gas pressure is controlled at 0.6 MPa. Zirconia balls are added as grinding media, and the ball-to-material ratio is adjusted to 15:1. The speed of the planetary ball mill is controlled at 250 r / min and the dispersion mixing time is 3 h to obtain a uniformly dispersed composite powder. The uniformly dispersed composite powder is then added to a mixing equipment in a mixer. Argon gas (99.99% purity, flow rate 5 mL / min) was introduced for protection. At the same time, a dispersant and a binder were added. The dispersant was stearic acid, and the mass of the dispersant added was 0.1% of the total mass of the composite powder. A paraffin-polyethylene-stearic acid composite binder (the ratio of paraffin, polyethylene and stearic acid was the same as in Example 1) was added at 15% of the total mass of the composite powder. Under the protection of inert gas, the mixing temperature was 160°C, the stirring speed was 50 r / min, and the mixing time was 40 min. After mixing evenly, the mixture was cooled to room temperature in the furnace to obtain a composite powder with uniform composition. (3) Powder injection molding: Add the composite material powder obtained in step (2) into the injection molding machine, set the injection temperature to 150℃, the injection pressure to 100MPa, and the holding time to 20s, inject it into the mold, cool it to room temperature and demold to obtain the molded blank. (4) Degreasing and sintering: The shaped green body is placed in a degreasing furnace. First, in an air atmosphere, the temperature is raised to 150°C at 8°C / min and held for 3 hours to remove the low-melting-point binder. Then, argon gas (purity 99.99%, flow rate 8 mL / min) is introduced and the temperature is raised to 500°C at 12°C / min and held for 4 hours to remove the high-melting-point binder, thus obtaining a degreased green body. (5) Hydrogen reduction sintering: The degreased green body is transferred to a reduction sintering furnace, high-purity hydrogen gas (flow rate 10 mL / min) is introduced, the temperature is raised to 850℃ at 8℃ / min and held for 60 min; then the temperature is raised to 1200℃ at a heating rate of 8℃ / min and held for 3 h to optimize the interface bonding and obtain the reduction sintered green body. In this example, the diamond / copper composite material was prepared at too high a temperature during reduction sintering, resulting in the extensive carbonization of diamond and loss of its original properties, making it impossible to perform subsequent processing and testing.
[0106] Performance testing: The following test methods were used to test various properties of the diamond / copper composite materials prepared in Examples 1-2 and Comparative Examples 1-2, respectively: Thermal conductivity: Tested according to the test method described in GB / T 22588-2008 standard; Mechanical properties: Tested according to the test methods described in GB / T 228.1-2021 standard; Density: Tested according to the test method described in GB / T 1033.1-2008 standard; The properties of the diamond / copper composite materials prepared in Examples 1-2 and Comparative Examples 1-2, as measured by the above testing methods, are shown in Table 1 below.
[0107] Table 1. Properties of Diamond / Copper Composite Materials
[0108] As shown in Table 1, when the content of Mo is in the range of 0.3% to 3%, the thermal conductivity, tensile strength and flexural strength of the composite material can be significantly improved. Specifically, the thermal conductivity of the diamond / copper composite material prepared in Examples 1-2 of this invention is 650-682 W / (m·K), the tensile strength is 220-242 MPa, the flexural strength is 322-327 MPa, and the density is ≥99%.
[0109] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A diamond / copper composite material, characterized in that: Includes a copper matrix and diamond particles and nano-Mo particles distributed within the copper matrix; The mass of the nano-Mo particles is 0.3-3% of the total mass of the diamond / copper composite material; The mass of the diamond particles is 25-50% of the total mass of the diamond / copper composite material; The diamond / copper composite material contains 47-74.7% copper by mass.
2. The diamond / copper composite material according to claim 1, characterized in that: The diamond / copper composite material has at least one of the following characteristics: (a1) The density of the diamond / copper composite material is ≥99%; (a2) The thermal conductivity of the diamond / copper composite material is 600-750 W / (m·K); (a3) The tensile strength of the diamond / copper composite material is 200-300 MPa; (a4) The flexural strength of the diamond / copper composite material is 300-400 MPa.
3. The diamond / copper composite material according to claim 1, characterized in that: The average particle size of the nano-Mo particles is 30-150 nm. And / or, the average particle size of the diamond particles is 80-120 μm.
4. The method for preparing the diamond / copper composite material according to any one of claims 1-3, characterized in that, Includes the following steps: The raw materials, including copper powder, diamond powder and molybdenum powder, are subjected to two-stage grinding to obtain composite powder; The composite powder is mixed with a dispersant and a binder and then kneaded to obtain a composite material; the composite material is then subjected to powder injection molding to obtain a preform. The shaped green body is degreased and then reduced sintered in a hydrogen atmosphere to obtain a sintered green body. The sintered green body is subjected to hot isostatic pressing and then cooled to obtain the diamond / copper composite material. The reduction sintering temperature is ≤1100℃.
5. The method for preparing the diamond / copper composite material according to claim 4, characterized in that, The reduction sintering process specifically involves: first, heating the degreased preform to 750-850℃ for the first sintering, and then heating to 900-1020℃ for the second sintering.
6. The method for preparing the diamond / copper composite material according to claim 4, characterized in that, The hot isostatic pressing process has at least one of the following characteristics: (b1) The temperature of the hot isostatic pressing treatment is 900-1000℃; (b2) The pressure of the hot isostatic pressing treatment is 80-150 MPa; (b3) The holding time for the hot isostatic pressing treatment is 2-4 hours; (b4) The pressurization rate of the hot isostatic pressing treatment is 5~10 MPa / min.
7. The method for preparing the diamond / copper composite material according to claim 4, characterized in that, The secondary grinding process involves first ball milling at a rate of 50-180 r / min, followed by a second ball milling at a rate of 150-250 r / min under protective gas to obtain the composite powder.
8. The method for preparing the diamond / copper composite material according to claim 4, characterized in that, The degreasing process involves: first, degreasing is carried out in air at 120-180°C, followed by a second degreasing in an inert atmosphere at 400-600°C.
9. A heat dissipation component, characterized in that: The heat dissipation component is made of the diamond / copper composite material as described in any one of claims 1-3.
10. The application of the diamond / copper composite material according to any one of claims 1-3 in the fields of aerospace, electronic packaging or new energy.